Rowing with MVN (2009)
In collaboration with Dutch rowing clubs of Protheus (Delft), Euros (Enschede), the Free University of Amsterdam, Delft Technical University and the Dutch Olympic Committee (NOC/NSF), RRD is currently investigating the technological and methodological (im)possibilities for coaching in competitive rowing. The aim is to develop a tool that provides sufficiently accurate, relevant information to the rowing coach about the exact movements, timing and behavior of the rowers during actual rowing on the water. Such information is otherwise very hard or even impossible for the rowing coach to obtain and assess. This valuable source of information is available to the coach on which to specify coaching decisions and activities. Moreover, the tool can be used in real time, or, if desired, in discussions with the rowers afterwards.